2022
DOI: 10.1080/21655979.2022.2084423
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of serum ATPase and AMPase in predicting diagnosis of colorectal cancer patients

Abstract: Colorectal cancer (CRC) is a common gastrointestinal cancer with high incidence and mortality rates. CRC may be associated with regulation of circulating nucleotides. This study aimed to evaluate the serum levels of nucleotide-metabolizing enzymes (ATPase and AMPase) in patients with CRC and to explore the clinical diagnostic value of these enzymes. The gene set variation analysis (GSVA) score of the ATP-adenosine signature was calculated using tumor samples from The Cancer Genome Atlas (TCGA). ATP-adenosine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…As mentioned earlier, kinases are well-known as attractive targets for drug discovery and biomarkers for disease. Recently, there have been several reports on the potential role of ATPase and AMPase , in the blood as cancer biomarkers. In these reports, blood samples from prostate cancer patients or colorectal cancer patients showed elevated ATPase and AMPase activities when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, kinases are well-known as attractive targets for drug discovery and biomarkers for disease. Recently, there have been several reports on the potential role of ATPase and AMPase , in the blood as cancer biomarkers. In these reports, blood samples from prostate cancer patients or colorectal cancer patients showed elevated ATPase and AMPase activities when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports on the potential role of ATPase and AMPase , in the blood as cancer biomarkers. In these reports, blood samples from prostate cancer patients or colorectal cancer patients showed elevated ATPase and AMPase activities when compared with healthy controls. Single-molecule profiling of ATPases and kinases in blood samples may be the next challenge for our digital cascade assay.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, preliminary studies reported that CD73 was upregulated and high CD73 on CRC cells promotes cell growth [14,15]. Serum samples from CRC patients presented higher CD73 activity than those from healthy controls [16]. However, it is still unclear whether CD73 could facilitate the development and immunosuppression of CRC, as well as the underlying regulatory mechanism.…”
Section: Ivyspring International Publishermentioning
confidence: 99%